Expression of Verbal Creativeness of I-II Classes’ Schoolchildren Having Speech Disorders - Domeikienė, Kristina (Acta Paedagogica Vilnensia, 2002)
In this article it was tried to reveal the peculiarities of development of verbal creativeness of I-II classes' schoolchildren having speech disorders. While trying to reach this goal firstly the conception of verbal creativeness was revealed, the main manifestations of verbal creativeness of schoolchildren of this age having speech disorders are singled out. The model of verbal creativeness of schoolchildren of younger age having speech disorders is made. Basing on the created model the scale of the main manifestations of verbal creativeness was made in order to evaluate the significance of the most important manifestations of verbal creativeness, and its (scale) reliability is checked with the help of statistical analysis. With the help of factor analysis the main features of verbal creativeness, that is eloquence, originality and flexibility are being described and singled out. Factor of expressing the degree of internal coordination of the scale of manifestations of verbal expression (Cronbach alfa) is being found. Characteristic of verbal creativeness of I-II classes' schoolchildren having speech disorders is presented in the article. It reflects the peculiarities of verbal creativeness of the studied schoolchildren not only with respect to age, but also to sex and place of residence. It was also tried to compare the expression of verbal creativeness of the schoolchildren of the mentioned age having and not having speech disorders and to reveal the same tendency of manifestations of the verbal creativeness manifcsting themselves in both groups of the schoolchildren.
Keywords: Creativity; verbal creativeness; speech disorders; verbal expression.